The Anxious and the Climbers: Ambivalent Attitudes towards Democracy among South Africa's Middle Class - Simone Schotte (German Institute of Global and Area Studies (GIGA), 2017)
Beyond the hopes placed in Africa's emergent middle class as an engine of economic growth, some analysts see this group as a bastion of political stability and enduring democratisation across the continent. This paper's approach differs from that of most studies, which treat the middle class as a homogeneous group, through two key contributions. First, using cluster analysis, I propose a novel way of conceptualising social class that broadly draws on the Weberian idea of shared life chances. I apply this method to South Africa and identify five social classes characterised by their members' living standards, overall life satisfaction, and self-perceived upward mobility. Second, the empirical analysis reveals significant discrepancies in attitudes towards democracy between the downwardly and upwardly mobile strata of the middle class, which I term the "anxious" and the "climbers", respectively. On the one hand, the "climbers" show the highest generic support for democracy as a form of government, whereas the "anxious" middle class displays feelings of resignation. On the other hand, I find indicative evidence of a status-quo bias among the "climbers". Rather than assuming a more demanding or critical stance in politics, they allow their political priorities to be at least partly shaped by an interest in securing and expanding attained living standards; being upwardly mobile is even associated with a higher tolerance for government attempts to constrain freedom of information, opinion, or expression.
Keywords: 300; South Africa; middle class; democratic consolidation; political attitudes